1993
DOI: 10.1007/bf02545364
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of cationic surfactants containing a disulfide bond

Abstract: Two new cationic surfactants containing a disulfide bond were synthesized, and the physical chemical characteristics and the fundamental surface‐active properties were determined. These new surfactants have potential applications in the textile and cosmetic field. These compounds have been prepared by condensation of a commercial Nα,Nα‐dimethyl amino betaine with cystine dimethyl ester or cystamine by means of the mixed anhydride method. The study of their properties revealed that these molecules are soluble i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…The surface excess, Γ, at the air-water interface was calculated by applying the Gibbs adsorption isotherm equation: Γ = -(1/n 2.303 RT) (dγ/d log C), where γ is the surface tension and C is the surfactant concentration, and n equals 2, since this value was found for ionic surfactants (15,16). The area per molecule at the interface was calcu-…”
Section: Resultsmentioning
confidence: 99%
“…The surface excess, Γ, at the air-water interface was calculated by applying the Gibbs adsorption isotherm equation: Γ = -(1/n 2.303 RT) (dγ/d log C), where γ is the surface tension and C is the surfactant concentration, and n equals 2, since this value was found for ionic surfactants (15,16). The area per molecule at the interface was calcu-…”
Section: Resultsmentioning
confidence: 99%
“…The constant n takes the value 2 for an ionic surfactant where the surfactant ion and the counterion are univalent and the value 3 for a dimeric surfactant made up of a divalent surfactant ion and two univalent counterions, in the absence of a swamping electrolyte. The reported a values were calculated on the basis of n = 2 (13,(23)(24)(25), on the assumption that one of the two charged groups is neutralized by a bound counterion, or n = 3, on the assumption of a full dissociation of the dimeric surfactants (16,17,(26)(27)(28)(29). Some studies reported two sets of values of a based on n = 2 and 3 (15,30).…”
Section: Aqueous Dimeric Surfactant Solutions At Concentrations Bmentioning
confidence: 99%
“…Cationic lipids derived from N-oleyl cysteine linked through a tripeptide are known to exhibit pH-sensitive hydrolysis when pH decreased from 7.5 to 5.5, which is the pH characteristic of the endosomal/lysosomal compartment, thus being potential transfection agents in gene therapy [42]. The cationic charge of amino acid-based surfactants such as (C 12 Cys) 2 is due to protonated amino groups of the cysteine residues (pK a 10.70) and the behaviour of the surfactant is pH-dependent, which is not the case of DABC and DABK that contain quaternary ammonium groups [11,40,41]. Thus, (C 12 Cys) 2 is expected to be essentially in its protonated form in PBS (pH 7.4) medium, although significant pK a shifts have been reported for amino acid-based gemini surfactants upon micellization as aggregation can induce changes in surfactant protonation [37,[43][44][45][46].…”
Section: Surface Tension Datamentioning
confidence: 99%
“…The surface tension at the CMC is a measure of the effectiveness of the surfactant, thus (C 12 Cys) 2 , with a cmc of 31.6 mN m −1 , is more efficient in surface tension reduction than 12-s-12, with cmc values in the range [35][36][37][38][39][40][41][42][43] mN m −1 [34] or DABC ( cmc 35 mN m −1 ) [41]. DABK and C n (C 12 Arg) 2 have cmc values around 30 mN m −1 [41,47] similar to (C 12 Cys) 2 .…”
Section: Surface Tension Datamentioning
confidence: 99%
See 1 more Smart Citation